2023
DOI: 10.30564/jsbe.v6i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Banking and Commercial Bank Performance Nexus in Zimbabwe (2011-2021): Impact and Implications

Abstract: The study investigated mobile banking and commercial banks’ performance nexus in Zimbabwe for the period 2011-2021. The investigation employed a pragmatic approach and a descriptive design. Primary data as well as secondary data were used to achieve the study objectives. Questionnaires, interviews and documentary guides were used to collect primary and secondary data respectively. There were 108 questionnaires distributed to staff members and customers of 6 sampled commercial banks in Zimbabwe having mobile ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, Makumbe et al [ 76 ] examined the performance of commercial banks during the multi-currency system in Zimbabwe using a dynamic panel-data model and found that the effect of the multiple currency system on commercial bank performance is weak. Recently, Makurumidze & Rwodzi [ 77 ] examined the effect of mobile banking on Zimbabwean commercial bank performance and found that mobile banking enhances performance through easy and cheaper access to services.…”
Section: Related Literaturementioning
confidence: 99%
“…Moreover, Makumbe et al [ 76 ] examined the performance of commercial banks during the multi-currency system in Zimbabwe using a dynamic panel-data model and found that the effect of the multiple currency system on commercial bank performance is weak. Recently, Makurumidze & Rwodzi [ 77 ] examined the effect of mobile banking on Zimbabwean commercial bank performance and found that mobile banking enhances performance through easy and cheaper access to services.…”
Section: Related Literaturementioning
confidence: 99%